Morphologic patterns and imaging features of intracranial hemangiopericytomas: a retrospective analysis - Pang, Haopeng (Onco Targets Ther, 2015)
OBJECTIVES: Hemangiopericytomas (HPCs) are rare intracranial tumors. Their differential diagnosis using computed tomography (CT) and magnetic resonance imaging (MRI) is difficult because of similarities in morphologic features with other intracranial tumors and meningiomas. METHODS: We retrospectively analyzed the clinical data and CT and MRI findings of 32 patients diagnosed with HPCs via histopathology. We evaluated the location, shape, morphologic patterns, density, and signal intensity of the tumors and classified them into four types. RESULTS: The number of tumors analyzed was 32; 29 were supratentorial and three were infratentorial. Eighteen tumors were lobular, while 14 were oval in shape. Further, 28 tumors had cystic areas, and 16 had signal-void vessels. Among the 20 tumors that had been scanned by MRI; eleven showed isointensity, eight slight hyperintensity, and one slight hypointensity on T1-weighted image. Moreover, 12 showed isointensity, and eight showed slight hyperintensity on T2-weighted image and T2-weighted-fluid-attenuated-inversion recovery. Diffusion-weighted images showed isointensity (9/13) or slight hyperintensity (4/13). Of the 15 tumors scanned by contrast-enhanced MRI, one showed poor enhancement; six, moderate enhancement; and eight, intense enhancement. Only one tumor exhibited the “dural tail” sign. Moreover, calcification was observed in just one tumor on CT imaging (1/22). All tumors (5/5) showed intense enhancement on CT angiography, whereas some exhibited dual blood supply (2/5). CONCLUSION: We conclude that tumors present outside the brain parenchyma, with isointense to slightly intense regions on MRI scans, oval/lobular shape, well-/ill-defined margins, signal-void vessels, apparent cystic areas, dual blood supply, and intense enhancement on CT or MRI scans, but without calcification or a “dural tail” sign, may be diagnosed as HPCs.